Screening of genes related to inorganic phosphate in families with primary brain calcifications (PBC) - FERREIRA, Joana Braga de Moraes Marques (2016)
Primary brain calcification (PBC), also known as idiopathic brain calcification or Fahr's disease, is a rare neurological condition that is characterized by calcium phosphate deposits in the basal ganglia and adjacent areas, movement disorders, headache and neuropsychiatric symptoms. It presents autosomic dominant inheritance and it is associated with two inorganic phosphate transporter coding genes: SLC20A2 and XPR1. Two other genes related to the blood-brain barrier maintenance and integrity are also linked to PBC, the platelet-derived growth factor-β and its receptor (PDGFB and PDGFRB), although their roles in the formation mechanism of the calcifications is not clear yet. For this study, besides the four genes above mentioned, other members of the platelet-derived grown factor family (PDGFA, PDGFRA, PDGFC and PDGFD) have also been selected as candidate genes, for which new primer pairs were designed. All genes above were screened for new variants by Sanger sequencing in fifteen Brazilian unrelated patients with brain calcifications. Sequence in silico analysis was performed using CLC Main Workbench 6.9 software and online tools available in NCBI and GOLDENPATH platforms, resulting in the identification of the first de novo SLC20A2 mutation in a patient diagnosed with PBC (NM_006749.4:c.1158C>G; NP_006740.1:p.Y386*). SLC20A2 is to-date the main gene associated with PBC, with affecting-variants observed in ~50% cases. In order to find SLC20A2 deletions and/or duplications not detected by sequencing, all Brazilian probands were screened by QMPSF (Quantitative Multiplex PCR of Short fluorescent Fragments) and a duplication of the terminal exon was found in a patient with brain calcifications and hyperparatiroidism. Simultaneously, twenty-four French unrelated patients with PBC were also analyzed by QMPSF and partial SLC20A2 deletions were detected in four patients: two with deletion of the exon 2, where the start codon is located; one with deletion of the exon 4; and one with deletion of exons 4 and 5. These results reinforce SLC20A2 role as the main gene associated to PBC, as well as demonstrate that copy number variation analyses, even when revealing only partial deletions or duplications of a gene, are complementary to sequencing and work side by side in the search of genetic variations involved in this disease.